The effect of alkali treatment to mechanical properties of resin composite reinforced with coir coconut fiber / Hadi Pranoto and Muhamad Fitri - Pranoto, Hadi; Fitri, Muhamad (Universiti Teknologi MARA, 2022)
Previous research related to the effect of alkali treatment on mechanical properties of composite materials which generate the regression model is still rare. From the previous research, alkali treatment does not always improve the mechanical properties of composite materials. Therefore, it is necessary to research to make sure the effect of alkali treatment on coconut fiber composite. This study aims to examine the effect of alkali treatment of fiber combined with fiber weight content on the mechanical and physical properties of epoxy resin matrix composite. Mechanical properties testing is done by impact test and torsion test. The fracture surface was observed using optical microscopy. Data from the test results were analyzed to see the effect of alkali treatment on the mechanical properties of the resulting composite material by generating the regression model of impact strength and shear strength for treated and untreated fiber composites. The coefficient of determination (R2) of all models was 1. This study obtained that the untreated fibers have better impact strength and shear strength than the treated ones. The highest impact strength, 7.07 kJ.m2, and the highest shear strength, 1.81 MPa were obtained from the samples containing 4% untreated fibers.